AMP-activated protein kinase, stress responses and cardiovascular diseases - Shaobin Wang; Ping Song; Ming-Hui Zou (2012)
AMPK (AMP-activated protein kinase) is one of the key players in maintaining intracellular homoeostasis. AMPK is well known as an energy sensor and can be activated by increased intracellular AMP levels. Generally, the activation of AMPK turns on catabolic pathways that generate ATP, while inhibiting cell proliferation and biosynthetic processes that consume ATP. In recent years, intensive investigations on the regulation and the function of AMPK indicates that AMPK not only functions as an intracellular energy sensor and regulator, but is also a general stress sensor that is important in maintaining intracellular homoeostasis during many kinds of stress challenges. In the present paper, we will review recent literature showing that AMPK functions far beyond its proposed energy sensor and regulator function. AMPK regulates ROS (reactive oxygen species)/redox balance, autophagy, cell proliferation, cell apoptosis, cellular polarity, mitochondrial function and genotoxic response, either directly or indirectly via numerous downstream pathways under physiological and pathological conditions.